2015
DOI: 10.1103/physrevb.91.094406
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature spin-glass behavior in a diluted dipolar Ising system

Abstract: Using Monte Carlo simulations, we study the character of the spin-glass (SG) state of a sitediluted dipolar Ising model. We consider systems of dipoles randomly placed on a fraction x of all L 3 sites of a simple cubic lattice that point up or down along a given crystalline axis. For x 0.65 these systems are known to exhibit an equilibrium spin-glass phase below a temperature Tsg ∝ x. At high dilution and very low temperatures, well deep in the SG phase, we find spiky distributions of the overlap parameter q t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Recently, spin glasses (SG) have attracted much attention and stimulated intensive studies because the combination of quenched spin spatial randomness and frustration create a complex free energy landscape with multiple local energy minima and finding the stable spin states formidable challenging 1 2 3 . In spite of many theoretical attempts of developing renormalization group 1 4 , mean-field approximation 5 and Monte Carlo simulation 3 6 7 8 based analyses, the low-temperature ( T ) spin phases as well as the out-of-equilibrium aging dynamics of such materials remain matters of strong debates. Not surprisingly, the complex nature of SG spin structures gives rise to the unique and diverse macroscopic properties in many fields of science.…”
mentioning
confidence: 99%
“…Recently, spin glasses (SG) have attracted much attention and stimulated intensive studies because the combination of quenched spin spatial randomness and frustration create a complex free energy landscape with multiple local energy minima and finding the stable spin states formidable challenging 1 2 3 . In spite of many theoretical attempts of developing renormalization group 1 4 , mean-field approximation 5 and Monte Carlo simulation 3 6 7 8 based analyses, the low-temperature ( T ) spin phases as well as the out-of-equilibrium aging dynamics of such materials remain matters of strong debates. Not surprisingly, the complex nature of SG spin structures gives rise to the unique and diverse macroscopic properties in many fields of science.…”
mentioning
confidence: 99%
“…This SG phase is similar to the one found in systems of Ising dipoles with strong structural disorder. In particular, this type of phases have been seen in textured systems with strong dilution, 39,43 as well as in dense non-textured systems, that is with high disorder in the frozen directions of the Ising dipoles. With the data gathered so far we can find the contours of the several FM and SG phases.…”
Section: 28mentioning
confidence: 87%
“…The thermal equilibration times t 0 were estimated after examining the plateaux for large time t of the overlap parameter q (see next Section) starting from different ini-tial configurations as described at length in Refs. 18,39 We also verify the symmetry in the thermal distributions of magnetization and the SG overlap parameter under the global inversion {σ i } → {−σ i } as an additional check that all samples are well equilibrated. 18 We used the first t 0 MC sweeps to equilibrate the samples and all thermal averages were extracted in the interval [t 0 , 2t 0 ].…”
Section: 38mentioning
confidence: 96%
“…In order to test the value thus obtained for t 0 , we observed that a second overlap q(t 0 , t 0 + t) calculated for pairs of configurations of a single replica taken at times t 0 and t 0 + t remains stuck to q 0 as t increases. 30 It is found that the less textured the system is, the longer the equilibration time appears. This is due to the large roughness of the free-energy landscapes for non-textured systems.…”
Section: 29mentioning
confidence: 99%